2021
DOI: 10.1039/d1ta01110c
|View full text |Cite
|
Sign up to set email alerts
|

Soft template-mediated coupling construction of sandwiched mesoporous PPy/Ag nanoplates for rapid and selective NH3 sensing

Abstract: Synchronous construction of heterogeneous materials from distinct molecular units into functional hybrids within one synthesis system holds large potential for customizing properties and applications, but which requires the elaborate coordination...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The high-intensity peak at 1559 cm À1 is attributed to the symmetric stretching of the aromatic C]C ring, the peak at 1345 cm À1 is related to the ring-stretching mode of PPy, the peak at 1053 cm À1 is attributed to C-H inplane deformation, and the peak at 940 cm À1 corresponds to the C]C backbone stretching, indicating the successful polymerization of PPy. [48][49][50] In addition to that, it can be seen that there are three distinct peaks at 471, 512 and 674.5 cm À1 , which are caused by Co 9 S 8 . [51][52][53] Meanwhile, the Fourier transform infrared (FTIR) spectra in Fig.…”
Section: Formation and Characterization Of Ncs/p-nmentioning
confidence: 82%
“…The high-intensity peak at 1559 cm À1 is attributed to the symmetric stretching of the aromatic C]C ring, the peak at 1345 cm À1 is related to the ring-stretching mode of PPy, the peak at 1053 cm À1 is attributed to C-H inplane deformation, and the peak at 940 cm À1 corresponds to the C]C backbone stretching, indicating the successful polymerization of PPy. [48][49][50] In addition to that, it can be seen that there are three distinct peaks at 471, 512 and 674.5 cm À1 , which are caused by Co 9 S 8 . [51][52][53] Meanwhile, the Fourier transform infrared (FTIR) spectra in Fig.…”
Section: Formation and Characterization Of Ncs/p-nmentioning
confidence: 82%
“…Self-assembly of block copolymers (BCPs) is a versatile method to construct diverse ordered nanostructures, [1][2][3][4][5][6] which provide ideal pore-directing soft templates for preparing porous materials. [7][8][9][10][11][12][13][14] For example, porous carbons have been broadly employed in energy storage and conversion devices thanks to their satisfied electrical conductivity, high specific surface area (SSA), and structural stability. [15][16][17] Among many energy conversion devices, fuel cells convert chemical energy to electrical energy, in which oxygen reduction reaction (ORR) is the key step DOI: 10.1002/marc.202100884 to achieve this conversion.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the molecular self‐assembly strategy using block copolymers as templates is a more promising method of preparing 2D mesoporous polymers. [ 19,25,36–38,43 ] For example, Feng and Mai et al. reported the one‐step synthesis of 2D mesoporous polypyrrole and polydopamine employing block copolymers polystyrene‐ b ‐poly(ethylene oxide) (PS‐ b ‐PEO) and P123 (poly(ethylene oxide) 20 ‐block‐poly(phenylene oxide) 70 ‐blockpoly(ethylene oxide) 20 ) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the molecular self-assembly strategy using block copolymers as templates is a more promising method of preparing 2D mesoporous polymers. [19,25,[36][37][38]43] For example, Feng and Mai et al reported the one-step synthesis of 2D mesoporous polypyrrole and polydopamine employing block copolymers polystyrene-b-poly(ethylene oxide) (PS-b-PEO) and P123 (poly(ethylene oxide) 20 -block-poly(phenylene oxide) 70 -blockpoly(ethylene oxide) 20 ) respectively. [43,45] However, the currently developed 2D mesoporous polymers are very limited owing to the following issues: a) Few types of precursor molecules and 2D substrates are available for polymers.…”
mentioning
confidence: 99%